Affordances as experienced by university faculties during and after the sudden transition to online teaching. Issue 2 (February 2023) - Alhosani, Najwa; Alsheikh, Negmeldin; Opoku, Maxwell Peprah; Takriti, Rachel; Aljneibi, Noof M.; Elhoweris, Hala; Garces-Bacsal, Rhoda Myra
Abstract: The ravaging effect of COVID-19 has been felt in all spheres of life. While countries are easing their restrictions, the remnants of COVID on education remain, with most universities formally embracing online teaching. Faculty have had to deal with this sudden and enduring transition to online teaching. Although some developments have been made with online education, enormous challenges are simultaneously reported in the literature. This mixed-method study aims to assess the essence of a faculty's bionetwork of lived experience after the sudden shift to online teaching due to the pandemic. Affordance theory was used as a theoretical lens to study the benefits, challenges, and opportunities associated with online education during and post-COVID. The study data comes from faculty members at one institution ( n = 170) and follow-up interviews with a smaller subset of participants from the same pool ( n = 10). Path analysis and mediation analysis revealed significant differences between the participants based on nationality and gender. While the findings supported two hypotheses, the third hypothesis was not supported. Overall, the findings showed both convergence and divergence between the qualitative and quantitative data. The study incorporates recommendations for online teaching, faculty well-being, and further research based on the results.